Insecticide resistance in the malaria vector Anopheles arabiensis in Mamfene, KwaZulu-Natal - Basil D. Brook; Leanne Robertson; Maria L. Kaiser; Eric Raswiswi; Givemore Munhenga; Nelius Venter; Oliver R. Wood; Lizette L. Koekemoer (South African Journal of Science, 2015)
The control of malaria vector mosquitoes in South Africa’s affected provinces is primarily based on indoor spraying of long-lasting residual insecticides. The primary vectors in South Africa are Anopheles arabiensis and An. funestus. South Africa’s National Malaria Control Programme has adopted a malaria elimination agenda and has scaled up vector control activities accordingly. However, despite these plans, local transmission continues and is most likely because of outdoor feeding by populations of An. arabiensis. An outdoor Anopheles surveillance system has been set up in three sections of the Mamfene district in northern KwaZulu- Natal in order to assess the extent of outdoor resting An. arabiensis in Mamfene and to assess the current insecticide susceptibility status of this population. According to WHO criteria, the An. arabiensis samples tested showed evidence of resistance to deltamethrin (pyrethroid), DDT (organochlorine) and bendiocarb (carbamate), and full susceptibility to the organophosphates pirimiphos-methyl and fenitrothion. Pre-exposure to piperonyl butoxide completely nullified the deltamethrin resistance otherwise evident in these samples, supporting previous studies implicating monooxygenase-based detoxification as the primary mechanism of pyrethroid resistance. The data presented here affirm the presence of pyrethroid and DDT resistance previously detected in this population and also indicate the comparatively recent emergence of resistance to the carbamate insecticide bendiocarb. These data show that special attention and commitment needs to be given to the principles of insecticide resistance management as well as to investigations into alternative control techniques designed to target outdoor-resting An. arabiensis in northern KwaZulu-Natal.